2010
DOI: 10.1080/15332640.2010.522889
|View full text |Cite
|
Sign up to set email alerts
|

Remission from Substance Dependence in U.S. Whites, African Americans, and Latinos

Abstract: We investigated remission from any type of substance dependence in Latinos, African Americans, and whites using the 2001-2002 National Epidemiologic Survey on Alcohol and Related Conditions, a national sample of community adults. Analyses focused on the 4,520 participants who indicated prior-to-last-year dependence on either alcohol or drugs. Outcome was categorized as current substance dependence or abuse, current use, or abstinence. Whites reported greater likelihood of substance dependence and African Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Other research indicates that European Americans compared to Latinos were more likely to remain abstinent after completing substance abuse treatment [ 11 , 12 ]. Other studies have shown similar outcomes for Latinos and other ethnic groups [ 13 16 ]. Finally, research supports different treatment outcomes among Latino subgroups and suggests that a number of individual characteristics may predict treatment outcomes among Latinos [ 17 ].…”
Section: Introductionsupporting
confidence: 56%
“…Other research indicates that European Americans compared to Latinos were more likely to remain abstinent after completing substance abuse treatment [ 11 , 12 ]. Other studies have shown similar outcomes for Latinos and other ethnic groups [ 13 16 ]. Finally, research supports different treatment outcomes among Latino subgroups and suggests that a number of individual characteristics may predict treatment outcomes among Latinos [ 17 ].…”
Section: Introductionsupporting
confidence: 56%
“…Although non-Whites experience remission from substance use disorders at rates comparable to Whites (Arndt, Vélez, Segre, & Clayton, 2010), AOD problems within communities of color have been historically portrayed in the mainstream media through a lens of pathology rather than through the perspectives of resilience, resistance, and recovery (White & Sanders, 2008). Pejorative racial stereotypes long embedded within antidrug campaigns in the United States have misrepresented the source, scope, and solutions to AOD-related problems within communities of color (Helmer, 1975;Leland, 1976;Musto, 1973;Neuspiel, 1996).…”
Section: Introductionmentioning
confidence: 97%